Influence integrated science model and implamantation learning with the unity of science in basic biology course to increase critical thinking - Nur Khasanah; Sajidan Sajidan; Sutarno Sutarno; Baskoro Baskoro (International Journal of Science and Applied Science: Conference Series, 2017)
This research purposed to investigate the effect of  integrated science model and its implementation in learning by Unity of Science in Basic Biology courses to improve students' critical thinking. This method research is a quasi-experimental with experimental design posttest only control group design. The population was all students of the first semester Biology, 2015/2016 academic year with consists  of  two classes.  Samples were taken with a simple random sampling technique. The data was collected using an open essay tests and observation of critical thinking skills. Data were analyzed with descriptive analysis and MANOVA test. The results showed as follows: (1) There are differences between the understanding of basic biology concepts students learn to use the integrated science model of with students who learn to use the direct teaching model (F = 7.783; p <0.05), (2) there are differences in thinking skills critical significantly between students learning with integrated science model and its implementation in Unity of science learning with students who learn to use the direct teaching model (F = 11.11, p <0.05).